Is SAFTA trade creating or trade diverting? A computable general equilibrium assessment with a focus on Sri Lanka - Bouët, Antoine; Mevel, Simon; Thomas, Marcelle (International Food Policy Research Institute, 2010)
The Agreement on South Asian Free Trade Area (SAFTA) entered its second phase of implementation in 2008. The creation of a free trade area is expected to affect its participants—Bangladesh, Bhutan, India, the Maldives, Nepal, Pakistan, and Sri Lanka—very differently given their diversity in terms of size, income, and structure of trade and protection. Using the 2004 MAcMapHS6-v2 database on measures of applied protection at the HS6 level and MIRAGE, a computable general equilibrium global model, this study examines the effects of SAFTA on trade and net income in the region. The magnitude of the effects will depend on initial levels of protection in the region and whether the agreement is trade diverting or trade creating. An important component of the SAFTA agreement is the exemption of products (sensitive list) from the trade liberalization process. Because such exclusion can restrict significantly the benefits from the regional trade agreement, we simulate the effects of SAFTA with and without sensitive products. Our findings show that among South Asian countries, Sri Lanka gains the most from the agreement because it initially has relatively low tariffs and faces high tariffs in the region. Exempting sensitive products from the agreement limits gains from trade for the lower-middle-income members of SAFTA but may be welfare enhancing for the least developed economies.